Rethinking the developmental state India's industry in comparative perspective - Pingle, Vibha (New Delhi Oxford University Press, 2000)
This book covers about the process of industrialization in newly industrializing countries.It examines why the same state has intervened in three industries with widely disarate levels of success.this book will be of great value to gratuate students and r
Keywords: Economic development-India; Industries-India; Industrialization